EFFECT OF INFORMATION FLOW SYSTEMS' AUTOMATION ON PERFORMANCE OF FINANCIAL MARKET INTERMEDIARIES IN KENYA - c, Dennis G.; Gathenya, Dr. Jane; Muturi, Dr.Willy (International Journal of Supply Chain Management, 2017)
Purpose: To determine the effect of information flow systems' automation on performance of financial market intermediaries in Kenya. Methodology: The study adopted a longitudinal approach, with study population being 218 employees in 109 financial market intermediary firms. The study used a census approach which greatly helps deal with the sampling errors involved in most studies of this kind. Additionally the study employed both primary and secondary data. Primary data was collected through questionnaire while secondary data was obtained from the firm's financial records. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive and inferential analysis was conducted to analyze the data while multiple and simple regression analysis was used to measure firms' performance as influenced by supply chain automation. The data was presented using tables, graphs and charts. Results: Based on the findings the study concluded that information flow processes influenced the performance of financial market intermediaries in Kenya. This can be explained by the regression results which showed that the influence was positive and also showed the magnitude by which information flow processes influenced the performance of financial market intermediaries. The regression results showed that information flow processes influenced the performance of financial market intermediaries by 0.169units. Unique contribution to theory, practice and policy: The study recommended for complete automation of information flow systems in the financial intermediaries. This will enhance making of informed decisions based which largely depends on the quality of information given. Also, information flow coordination among the trading partners is essential.